Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/su13126645
|View full text |Cite
|
Sign up to set email alerts
|

Can Talent Management Improve Training, Sustainability and Excellence in the Labor Market?

Abstract: The objective of this article is to analyze the characteristics of the most attractive companies in the labor market, which each year maintained their position in the ranking published by the Spanish business magazine Actualidad Económica (AE) for the period 2013–2020. The research study will focus on permanence in ranking, global valuation, and training. To do this, control variables were added: business management gender, geo-cultural areas, regional areas, economic activity, size and stock market membership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Indeed, in Table 4 it was observed that the companies in the ranking with greater female presence are better positioned in the ranking, according to Ferreiro-Seoane et al (2021) and Ferreiro-Seoane et al (2023b). This fact is reflected mostly in the Work Environment item where they express more intensity in favour of companies managed by women, but this fact does not seem to effectively promote this social objective.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, in Table 4 it was observed that the companies in the ranking with greater female presence are better positioned in the ranking, according to Ferreiro-Seoane et al (2021) and Ferreiro-Seoane et al (2023b). This fact is reflected mostly in the Work Environment item where they express more intensity in favour of companies managed by women, but this fact does not seem to effectively promote this social objective.…”
Section: Discussionmentioning
confidence: 96%
“…Digital technology has made it easier for all stakeholders in the value chain to connect. Remote collaboration, virtual processes, and real-time connections have brought unprecedented efficiency and convenience to enterprises [116]. Digital technology has also shown the advantages of high efficiency and energy conservation in product lifecycle management, which is essential for enterprise sustainability [117].…”
Section: Implication Of Agility In Sustainable Designmentioning
confidence: 99%
“…The newly revised vocational education law makes it clear that vocational education is an education type with the same important status as general education (Provisions, 1999). Vocational undergraduate needs the transformation of vocational education mode and the strengthening of the training paradigm of high-quality technical and skilled talents, which further defines the type orientation of vocational education (Ferreiro-seoane et al, 2021).…”
Section: Analysis On the Characteristics Of Vocational Education Unde...mentioning
confidence: 99%
“…The school should give full play to the radiation and demonstration role of model teachers. For example, the school can establish a "famous craftsman teacher" studio, select typical teachers through teacher skill competitions, famous teachers and other ways, give full play to the radiation and demonstration role of model teachers, and drive the overall quality improvement of the teaching team; Establish a teacher evaluation and promotion mechanism in line with the orientation of vocational education undergraduate type, improve the performance appraisal methods, improve the social status of teachers, improve the job attractiveness of vocational education undergraduate teachers, and implement the rights and interests protection and incentive mechanism (Ferreiro-seoane et al, 2021).…”
Section: (I)mentioning
confidence: 99%